Model Kolaborasi Orang Tua dan Pelayan Anak dalam Pertumbuhan Iman Anak Usia Pra Remaja Di GKII Imanuel Amborawang Darat - Tangel, Imelda; Boiliu, Esti Regina; Triposa, Reni (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2025)
This study aims to analyze the collaborative model between parents and childcare workers in the faith development of pre-adolescent children at GKII Imanuel Amborawang Darat. A descriptive qualitative approach was used, utilizing Bandura's social learning theory, Bronfenbrenner's human development ecology, and the concept of faith education according to Pazmino and Turansky & Miller as theoretical foundations. The results of the study indicate that effective collaboration between parents and childcare workers creates synergy in fostering children's faith through spiritual communication, living examples, and ongoing spiritual guidance. An integrated faith environment between home and church plays a crucial role in helping pre-adolescent children internalize Christian values. In facing the challenges of digital culture, this collaboration is key to strengthening the foundation of children's faith. This study emphasizes the importance of a strategic and sustainable partnership between families and churches in the process of forming children's faith, so that they can better face the various challenges of this digital era.